2001
DOI: 10.1210/jc.86.4.1496
|View full text |Cite
|
Sign up to set email alerts
|

One Year of Insulin-Like Growth Factor I Treatment Does Not Affect Bone Density, Body Composition, or Psychological Measures in Postmenopausal Women

Abstract: The activity of the hypothalamic-GH-insulin-like growth factor I (hypothalamic-GH-IGF-I) axis declines with age, and some of the catabolic changes of aging have been attributed to the somatopause. The purpose of this investigation was to determine the impact of 1 yr of IGF-I hormone replacement therapy on body composition, bone density, and psychological parameters in healthy, nonobese, postmenopausal women over 60 yr of age. Subjects (n = 16, 70.6 +/- 2.0 yr, 71.8 +/- 2.8 kg) were randomly assigned to either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 0 publications
1
54
0
1
Order By: Relevance
“…In a placebo-controlled trial, Papadakis et al examined the effects of GH administration for 6 months (0.27 IU/kg/week) in healthy elderly men (mean age 75 years) with low IGF-I levels (90) and Friedlander et al studied the effects of IGF-I in postmenopausal women over 60 years of age for one year in a placebo-controlled study (91). In both trials, no effect Figure 2 Effect of GH replacement on measures of attention.…”
Section: Effects Of Growth Hormone or Insulin-like Growth Factor-i Thmentioning
confidence: 99%
“…In a placebo-controlled trial, Papadakis et al examined the effects of GH administration for 6 months (0.27 IU/kg/week) in healthy elderly men (mean age 75 years) with low IGF-I levels (90) and Friedlander et al studied the effects of IGF-I in postmenopausal women over 60 years of age for one year in a placebo-controlled study (91). In both trials, no effect Figure 2 Effect of GH replacement on measures of attention.…”
Section: Effects Of Growth Hormone or Insulin-like Growth Factor-i Thmentioning
confidence: 99%
“…These conflicting results plus the necessity for administration by injection make it unlikely that GH will become a therapeutic option for patients with osteoporosis who are not GH deficient. IGF-1 therapy does not appear to be effective [21].…”
Section: Folate/vitamin B 12mentioning
confidence: 99%
“…These conflicting results plus the necessity for administration by injection make it unlikely that GH will become a therapeutic option for patients with osteoporosis who are not GH deficient. IGF-1 therapy does not appear to be effective [21].Androgens: Because men have higher bone density than women, it has been suggested that treatment with androgens might benefit women with osteoporosis. However, the effect of treatment with androgen plus estrogen on bone mineral density does not appear superior to the effect of estrogen alone and androgen has unwelcome virilizing effects [22].…”
mentioning
confidence: 99%
“…IGF1 treatment in adults has been evaluated in a few studies. In postmenopausal women treated with IGF1 alone, glucose tolerance improved (7) and in insulin-resistant individuals insulin sensitivity increased (8). IGF1 in combination with GH in healthy volunteers and patients with traumatic brain injury enhanced GH's anabolic effects (9,10) and in post-menopausal women led to fat mass reduction (11).…”
Section: Introductionmentioning
confidence: 99%